Exploring Spirituality of Sa‘dūn al-Majnūn’s Poetry: A Perspective of Ibn ‘Arabī’s Hermeneutics - Abyad, Habil; Muassomah; Haque, Arina; Tsauro, M. Ahalla; Syaifuddin, Helmi (Al-Ma‘rifah, 2022)
Spirituality poetry generally contains elements of beauty and aesthetics, so it tends to display linguistics and literature. Sa‘dūn’s poetry has its uniqueness with spiritual content in it. Spirituality in Sa‘dūn’s poetry describes the close relationship between man and God, which is reflected in the form of criticism of society. Therefore, this study aims to determine the form of spirituality in Sa‘dūn’s poetry. This research method uses content analysis by using Ibn ‘Arabī’s hermeneutics approach in its interpretation. The results of this study indicate two things, namely: (1) essence of death in the first poem contains three important pieces of advice, namely life in this world, life in the afterlife, and prepare for death; and (2) essence of ma‘rifah contained in the second Sa‘dūn’s poetry shows Sa‘dūn’s closeness to God as evidenced by two things, namely zuhud and world prevents towards Allah. This study is important in expanding the study of Ibn ‘Arabi’s hermeneutics which is usually only used to interpret the inner meaning in the Qur’ān and ḥadīth. Hermeneutics can also be used in other literary works such as poetry, novels, short stories, etc.